A blinded clinical study using a subepidermal moisture biocapacitance measurement device for early detection of pressure injuries. Issue 3 (21st January 2020) - Okonkwo, Henry; Bryant, Ruth; Milne, Jeanette; Molyneaux, Donna; Sanders, Julie; Cunningham, Glen; Brangman, Sharon; Eardley, William; Chan, Garrett K.; Mayer, Barbara; Waldo, Mary; Ju, Barbara
Abstract: This study aimed to evaluate the sensitivity and specificity of subepidermal moisture (SEM), a biomarker employed for early detection of pressure injuries (PI), compared to the "Gold Standard" of clinical skin and tissue assessment (STA), and to characterize the timing of SEM changes relative to the diagnosis of a PI. This blinded, longitudinal, prospective clinical study enrolled 189 patients (n = 182 in intent‐to‐treat [ITT]) at acute and post‐acute sites (9 USA, 3 UK). Data were collected from patients' heels and sacrums using a biocapacitance measurement device beginning at admission and continuing for a minimum of 6 days to: (a) the patient developing a PI, (b) discharge from care, or (c) a maximum of 21 days. Standard of care clinical interventions prevailed, uninterrupted. Principal investigators oversaw the study at each site. Blinded Generalists gathered SEM data, and blinded Specialists diagnosed the presence or absence of PIs. Of the ITT population, 26.4% developed a PI during the study; 66.7% classified as Stage 1 injuries, 23% deep tissue injuries, the remaining being Stage 2 or Unstageable. Sensitivity was 87.5% (95% CI: 74.8%‐95.3%) and specificity was 32.9% (95% CI: 28.3%‐37.8%). Area under the receiver operating characteristic curve (AUC) was 0.6713 (95% CI 0.5969‐0.7457, P  < .001). SEM changes were observed 4.7 (± 2.4 days) earlier than diagnosis of a PI via STA alone. Latency between the SEM biomarker and later onset of a PI, in combination with standard of care interventions administered to at‐risk patients, may have confounded specificity. Aggregate SEM sensitivity and specificity and 67.13% AUC exceeded that of clinical judgment alone. While acknowledging specificity limitations, these data suggest that SEM biocapacitance measures can complement STAs, facilitate earlier identification of the risk of specific anatomies developing PIs, and inform earlier anatomy‐specific intervention decisions than STAs alone. Future work should include cost‐consequence analyses of SEM informed interventions.